The origins of reporting bias: Selective but unbiased reporting by early-career researchers? - Anastasiya-Mariya Asanov Noha; Igor A. Asanov; Guido Bünstorf; Valon Kadriu; Pia Schoch (Philipps-University Marburg, School of Business and Economics, 2025)
Doctoral dissertations provide evidence about research practices in early-stage research. We examine reporting bias by manually collecting over 94,000 test statistics from a random sample of German dissertations and their follow-up papers worldwide. We observe selective reporting, as only a fraction of the tests in the dissertations is reported in follow-up papers. Unexpectedly, we find no increase in reporting bias in follow-up papers compared to dissertations nor, generally, reporting bias in dissertations or papers. Self-selection into higher-impact journals based on statistical significance may reconcile our finding of selective yet "unbiased" reporting with prior evidence suggesting pervasive reporting bias.
Keywords: A14; A23; C12; I23; 330; research transparency; reporting bias; higher education; young researchers